Yeast RAD3 protein binds directly to both SSL2 and SSL1 proteins: implications for the structure and function of transcription/repair factor b. - Bardwell, L (1994)
The RAD3 and SSL2 gene products are essential proteins that are also required for the nucleotide excision repair pathway. We have recently demonstrated that the RAD3 gene product along with the SSL1 and TFB1 gene products are subunits of RNA polymerase II basal transcription factor b. Additionally, the SSL2 gene product physically interacts with purified factor b. Here we combine an in vitro immunoprecipitation assay and an in vivo genetic assay to demonstrate a series of pairwise protein-protein interactions involving these components. RAD3 protein binds directly to both SSL2 protein and SSL1 protein in vitro. SSL1 protein interacts with itself and with RAD3 and TFB1 proteins in living yeast cells. An N-terminal, possibly noncatalytic, domain of SSL2 protein is sufficient for the factor b-SSL2 interaction, and a product of a DNA repair-defective allele of SSL2 is not defective in binding to factor b. We present genetic evidence suggesting that the DNA-repair function of SSL2 protein is not dependent on its essential function.